Projeto e implementação de um controlador PID digital para um sistema barra e bola - Iastrenski, Edgar Felix (2021)
In this work, a digital controller for a ball and beam system was designed and implemented. The controller aims to keep the ball balanced in a certain position on the beam, by acting on the beam’s tilt angle. A digital PID controller was designed using the root locus method, from the transfer function based on the mathematical modeling of the system. A prototype for the system was built, using a distance sensor to measure the ball’s position, a servo motor to adjust the beam’s tilt angle and a microcontroller to implement the digital control. Using the system prototype, some testes were performed to verify the controller’s performance, by applying a step on the system’s setpoint and by verifying the output’s behavior when a disturbance is applied on it. The designed controller proved to be effective in keeping the ball in the desired position, despite showing some differences in relation to the simulated settling time and overshoot of the closed loop system.